An epidemiological survey of oral mucosal lesions among elderly Malaysians - Taiyeb Ali, T.B.; Razak, I.A.; Raja Latifah, R.J.; Zain, R.B. (Wiley, 1995)
A house to house random survey on elderly subjects was undertaken in the District of Klang in Malaysia. The objective of this study was to investigate the prevalence of oral mucosal lesions (OML) among the elderly in this area. The primary units in the sampling frame were the Enumeration Blocks (EBs) as defined under the population census. All households of the selected EBs were considered as sampling units and members aged 60 and above were considered as respondents. There was a slight preponderance of females, with the Malays comprising the majority of the subjects. Of the 486 respondents, mean aged 69.1 +/- 7.3 yr, 111 had at least one oral mucosal lesion, a prevalence of 22.8. A total of 145 lesions were detected. The prevalence of OML was highest among Indians and least among the Chinese. The most common finding was tongue lesions, recording a prevalence of 10.7, followed by oral pigmentation (4.9) and white lesions (4.3). Denture related lesions were comparatively low at 2.5. Two cases of oral cancer if representative would give a relatively high prevalence of 0.4